Benznidazole therapy improves pressure overload and cardiac electrical profile in an experimental model of Angiotensin II infusion-induced hypertension: Mechanistic insights - Ana Paula da Silva Pinheiro; Glaucia Vilar-Pereira; Leda Castaño-Barrios; Isalira Peroba Rezende Ramos; Yasmin Pedra-Rezende; Luiza Dantas-Pereira; Rubem Figueiredo Sadok Menna-Barreto; Daniel Gibaldi; Hilton Antônio Mata-Santos; Joseli Lannes-Vieira (PLoS ONE, 2026)
High blood pressure is one of the leading global causes of cardiovascular diseases. The chronic action of high concentrations of angiotensin II (Ang II) promotes arterial hypertension. Ang II acts via AT 1 and AT 2 receptors. Acting via AT 1 R, Ang II can induce the production of inflammatory cytokines and reactive oxygen species, promoting oxidative stress, which may influence cardiac electrical traits. In hypertensive patients, a dispersed QTc interval may predict cardiovascular events and mortality. Benznidazole (Bz), an antiprotozoal prodrug, also has immunomodulatory properties. Here, we tested the idea that in a model of Ang II-induced BP overload, cardiomyopathy will be associated with a prolonged QTc interval. Then, we investigated the effects of Bz therapy on BP overload, electrical changes, and oxidant/antioxidant imbalance. C57BL/6 mice were implanted with an osmotic minipump containing Ang II or saline as a control. At 7 days post-surgery (dps), Ang II infusion increased mean BP, which was sustained until 28 dps. Further, the Ang II-infused group had prolonged QTc interval and QRS complex. Bz or the AT 1 R antagonist losartan (Los) were administered from 7 to 28 dps. Compared with the vehicle-treated group, Los therapy restored mean BP to normal but did not affect long-QTc. At 14 and 28 dps, Bz therapy improved BP, and restored QTc dispersion to normal, while improving RR interval and QRS complex changes. Ang II infusion increased IL-6 concentrations and oxidant/antioxidant imbalance in cardiac tissue. Bz therapy showed a beneficial effect, tending to restore the IL-6 concentrations and oxidant/antioxidant balance to physiological levels, which was correlated with reversal of the dispersed QTc interval. Altogether, our data support that Bz therapy deserves further evaluation as an anti-inflammatory and antioxidant adjuvant tool to improve BP overload and long-QTc syndrome underlying cardiovascular diseases.